2008
DOI: 10.1250/ast.29.86
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of the influence of room acoustics on the teacher's voice

Abstract: Teachers belong to the group of professional voice users who often suffer from voice disorders. A reduction of the voice capacity can impede or stop the exertion of their profession. One reason for a significantly increased prevalence of voice problems can be poor room acoustical conditions in the class rooms. About the half of the teachers of a secondary modern school in Aachen were investigated with respect to their voice status by using phoniatric, logopedic and objective voice analysis methods. The prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The measurements suggest that teachers from the test group made good use of the voice support as an adaptive mechanism to preserve their vocal health. This finding supports the results from a study by Kob et al [10], who found that teachers with voice problems were more affected by poor classroom acoustics than their healthy colleagues. The behavior of the teachers in the test group follows the results of Brunskog et al [11], who found that teachers lowered their voice levels as a function of the amplification offered by the room to their own voice.…”
Section: Discussionsupporting
confidence: 92%
“…The measurements suggest that teachers from the test group made good use of the voice support as an adaptive mechanism to preserve their vocal health. This finding supports the results from a study by Kob et al [10], who found that teachers with voice problems were more affected by poor classroom acoustics than their healthy colleagues. The behavior of the teachers in the test group follows the results of Brunskog et al [11], who found that teachers lowered their voice levels as a function of the amplification offered by the room to their own voice.…”
Section: Discussionsupporting
confidence: 92%
“…It can be noted that this was an entirely subjective study -no objective values were calculated from the simulated impulse responses. Kob et al 8 has presented results from a study where the voice status of 25 teachers were investigated using standard methods as applied by audimetrisists, phoniatricians and speech therapists, in addition to an acoustic analysis of speech and voice samples.…”
Section: Bistafa and Bradleymentioning
confidence: 99%
“…While the auditory-feedback manifestations of distinctive room-acoustic properties are likely to play a role in vocal accommodations (i.e., adapting the characteristics of voices to local circumstances) of occupational speech workers, 3,12,14 more research is needed to understand the specific effects. 15 The impact of classroom and other room acoustics on listeners has been thoroughly studied, especially regarding noise levels and speech intelligibility, [16][17][18] resulting in listener-focused standards and recommendations. 19,20 However, investigations regarding acoustic effects of classrooms and other settings on talkers are still limited.…”
Section: Introductionmentioning
confidence: 99%